PENGARUH PRICE PERCEPTION, SELF CONTROL, CONSUMER ENGAGEMENT DAN HEDONIC SHOPPING MOTIVATION TERHADAP IMPULSIVE BUYING DALAM FITUR LIVE SHOPPING TIKTOK - Oktafiani, Ananda; Dita Puruwita; Nofriska Krissanya (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
The rise of social commerce, particularly through the live shopping feature on Tiktok, hastransformed consumer behavior, especially in relation to impulsive buying. This study aims to analyze theinfluence of price perception, self-control, consumer engagement, and hedonic shopping motivation onimpulsive buying behavior within the context of Tiktok's live shopping feature in the Jakarta area. Aquantitative approach was employed using a survey method involving 180 Generation Z respondents whoactively use Tiktok Shop. Data were analyzed using Structural Equation Modeling (SEM) based on thePartial Least Squares (PLS) technique with the assistance of SmartPLS 4.0 software. The results revealthat price perception, consumer engagement, and hedonic shopping motivation have a positive andsignificant effect on impulsive buying. Conversely, self-control has a negative and significant effect,reaffirming its role as an internal factor capable of restraining impulsive urges. These findings align withthe Stimulus-Organism-Response (S-O-R) theoretical framework employed in this study. This researchcontributes to the digital consumer behavior literature and offers practical implications for marketers indesigning strategic interventions that ethically stimulate or manage impulsive purchasing behavior withinthe live commerce ecosystem.